Prediction of oil and gas occurrence in the Vilyui hemisineclise according to interpretation of geological and geophysical data and basin modeling (Republic of Sakha (Yakutia)) - M. O. Fedorovich; A. Yu. Kosmacheva (Georesursy, 2024)
The paper is aimed at the prediction of oil and gas occurrence of the Upper Permian, Lower Triassic and Lower Jurassic deposits in the Vilyui hemisineclise. The basin modeling research implies the Upper Paleozoic and Mesozoic petroleum system model of the Vilyui hemisineclise. The initial generation time at the bottom of the Permian source rock is 270 Ma. The most intense generation of hydrocarbons is found to be in the late Permian and early Triassic. The generation power of the Permian source rock is 800 trillion m3 . The hydrocarbon losses is up to 90% in consequence of unfavorable seal properties of the Lower Triassic and Lower Jurassic clay formations. All the potential hydrocarbon traps of the Vilyui hemisyneclise are considered to be formed during the Cretaceous stage of development. There is therefore an appropriate environment for the hydrocarbon accumulation to be in progress. The interpretation of geological and geophysical data identifies the areal extent prediction of sand reservoirs and overlying clay interlayers of high quality in the Upper Permian and Lower Triassic seals. The goal of a comprehensive approach to the sedimentary basin research is to divide the territory into oil and gas zones of various prospects in relation to the factors controlling hydrocarbon deposits.